2018
DOI: 10.1007/s13205-018-1442-5
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic detoxification of azo dyes by a multifarious Bacillus sp. strain MR-1/2-bearing plant growth-promoting characteristics

Abstract: This study was conducted to elucidate the inherent potential of Bacillus sp. MR-1/2, which was isolated from root zone of maize crop grown on a textile wastewater-irrigated soil. The isolated strain was identified through its ribosomal RNA sequence. Under in vitro conditions, the strain demonstrated its tolerance for high concentrations of various heavy metal ions as determined by minimum inhibitory concentration. Moreover, the strain MR-1/2 exhibited many important phytobeneficial traits such as inorganic P s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(49 reference statements)
3
11
0
Order By: Relevance
“…Moreover, the strain was positive for ACC deaminase activity at temperatures from 35 to 45°C. These results confirmed the findings of Shahid et al (2018).…”
Section: Biochemical Characterization Of the Bacterial Strain Bacillus Sp Mr-1/2supporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the strain was positive for ACC deaminase activity at temperatures from 35 to 45°C. These results confirmed the findings of Shahid et al (2018).…”
Section: Biochemical Characterization Of the Bacterial Strain Bacillus Sp Mr-1/2supporting
confidence: 91%
“…This might be due to the fact that the PhBR strain Bacillus sp. MR-1/2 was declared positive for P solubilization in a previous study (Shahid et al 2018) and showed higher P solubilization at temperature ranges from 35 to 45°C in vitro in present study. Our results are similar to those of previous studies where an increased available P contents in soil due to the application of phosphate solubilizing rhizobacteria was reported (Hussain et al 2016;Tahir et al 2018;Ijaz et al 2019).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, SK1 treated plants showed increased shoot and root growth in comparison to untreated as well as control water treated plants, likely due to the presence of PGPP in the spent media. IAA producing K. pneumoniae was found to induced rooting in Cicer arietinum which also contributed to toxicity reversal of azo dye 40 . In a previous study, seeds of S. vulgare and P. mungo exposed to untreated reactive black 5(RB5) exhibited 50% and 60% germination inhibition respectively as compared to exposure with S. halophila treated RB5 biodegradative metabolites 41 .…”
Section: Phytotoxicity Studymentioning
confidence: 97%
“…Genomic DNA extraction and amplification of 16S rRNA gene of the strain FSS2C were carried out as described by Shahid et al (2018a). The genomic DNA of strain FSS2C was isolated by the CTAB method as reported by Wilson (2001) and DNA was quantified through spectrophotometer using Nano Drop™ 2000/2000c (Thermo Fisher Scientific, USA).…”
Section: Taxonomic Identification and Phylogenetic Analysismentioning
confidence: 99%